THE INFLUENCE OF THE PROJECT-BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON THE ACID-BASE CONCEPT (A Case study at Senior High School No. 2 Medan) - Bangun, Prihatni Yoshepine; Eddiyanto, Eddiyanto; Munthe, Sitti Darna (FKIP USK, 2024)
The research aims to determine the effect of the project-based learning model on learning outcomes and students' responses to acid-base material. Based on observations and interviews with students and teachers, the background of this study is that chemistry education remains teacher-centered and lacks practical activities, partly due to the COVID-19 pandemic. It is hoped that this model will engage students more actively in the learning process and improve their learning outcomes. This experimental research employs a pretest-posttest control group design. The research samples were students from class XI IPA 2, who experienced the project-based learning model (experimental class), and class XI IPA 1, who followed the conventional model (control class). The instruments used in this study were tests to measure student learning outcomes and questionnaires to assess student responses to the implemented learning model. The normality test results showed a significant value of 7 for both the experimental and control classes at an alpha level of 0.05. The homogeneity test indicated a value of 1.08 at an alpha level of 0.05, suggesting the data are normally distributed and have homogeneous variance. The results of the right-sided t-test showed a significant value of 7.35, which is greater than the critical value of 1.669, indicating that t_count is greater than t_table, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha).